2021
DOI: 10.3389/fpls.2020.634819
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus subtilis SL18r Induces Tomato Resistance Against Botrytis cinerea, Involving Activation of Long Non-coding RNA, MSTRG18363, to Decoy miR1918

Abstract: Mounting evidence has indicated that beneficial rhizobacteria can suppress foliar pathogen invasion via elicitation of induced systemic resistance (ISR). However, it remains elusive whether long non-coding RNAs (lncRNAs) are involved in the mediation of the rhizobacteria-primed ISR processes in plants. Herein, we demonstrated the ability of the rhizobacterial strain Bacillus subtilis SL18r to trigger ISR in tomato plants against the foliar pathogen Botrytis cinerea. Comparative transcriptome analysis was condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 57 publications
0
12
0
Order By: Relevance
“…Plants possess their own defense system that includes physical, chemical, and induced defenses [182]. The latter is defined as "the process of active resistance dependent on the host plant's physical or chemical barriers, activated by biotic or abiotic inducing agents" [186].…”
Section: Induction Of Systemic Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…Plants possess their own defense system that includes physical, chemical, and induced defenses [182]. The latter is defined as "the process of active resistance dependent on the host plant's physical or chemical barriers, activated by biotic or abiotic inducing agents" [186].…”
Section: Induction Of Systemic Resistancementioning
confidence: 99%
“…Induced resistance is usually divided in two main groups, systemic acquired resistance (SAR) and inducible systemic resistance (ISR) [182]. The former can be defined as the inherent immunity of the plant, and it is activated either by direct exposure to biotic triggers, both pathogens and non-pathogens, or by abiotic factors, including a number of chemical compounds [1,199].…”
Section: Induction Of Systemic Resistancementioning
confidence: 99%
“…Similarly, B. velezensis strain FZB42 produces bacilysin, bacillaene, and diffcidin which suppress fire blight disease in plants [8]. Recently, it was reported that B. subtilis SL18r and B. simplex Sneb545 elicit induce systemic resistance in plants against Botrytis cinerea and Heterodera glycines, respectively [9,10]. Furthermore, volatile organic compounds such as acetoin and 2,3-butanediol have also been reported to trigger systemic resistance in plants [11].…”
Section: Introductionmentioning
confidence: 99%
“…It has been well demonstrated that several rhizobacterial strains can effectively prevent the infection of foliar and soil-borne pathogens by activating the induced systemic resistance (ISR) [3,4]. The rhizobacteriainduced ISR responses are widely present in various plant species, conferring the increased broad-spectrum resistance against pathogenic microbes such as viruses, bacteria and fungi [5][6][7][8]. The defense responses of plants triggered by rhizobacteria are not associated with direct activation of defense-related pathways, but precisely perceive bacteriaderived elicitors to provoke more efficient defense actions against pathogen infection [9].…”
Section: Introductionmentioning
confidence: 99%